Factors Affecting Systematic Risk of Saudi Industrial Stocks - Sallam, Osama Azmi (Journal of Economic, Administrative and Legal Sciences, 2020)
The objective of this study is to test the measurable effects of factors that might influence the systemic risk of the shares of Saudi industrial companies. These factors are: companies’ use of debt, companies’ profitability and companies’ liquidity. The study tested the relationship between the variables mentioned during the period June 2006 to July 2011, following Feb, 2006 crisis that hit the Saudi stock market. Using a linear multiple regression model, with an R square of 51%, the study concluded that there is a significant effect of the average debt ratio, average current ratio and average return on equity of Saudi industrial companies on these companies’ systematic risk represented by the beta coefficient of these shares.